Penerapan Metode Certainty Factor Untuk Diagnosis Penyakit Otitis Media Di Rumah Sakit Bhayangkara Bengkulu - Rahayu, Nengsi; Aspriono, Hari; lianda, Deri (UNIVED Press, 2025)
Bhayangkara Bengkulu Hospital is one of the private general hospitals and is one of the type C hospitals in the Bengkulu region. Bhayangkara Bengkulu Hospital provides health services supported by specialist doctor services and supported by other medical facilities. During 2023 at Bhayangkara Hospital, there were 272 patients who consulted doctors regarding Otitis Media (middle ear disease). Otitis media generally attacks children, especially under 6 years of age. The trigger is obstruction of the